Empirical models for calculating soil wetting patterns under surface drip irrigation systems: A comprehensive analysis - Li, Ge; Nie, Weibo; Li, Yuchen (Irrigation and drainage, 2025)
Accurate estimation of the surface wetted radius (R) and vertical wetted depth (Z) of wetting patterns in drip irrigation systems is crucial for ensuring that the designs of such systems are effective. This study compared 14 empirical models for estimating drip irrigation wetting patterns by assessing their accuracy using published measurement data and HYDRUS‐2D/3D simulations. The technique for order of preference by similarity to the ideal solution (TOPSIS) was employed to comprehensively rank the models. The results indicate that the empirical model proposed by Fan et al. (2023) (FY) exhibited the highest accuracy when the estimations of R and measured and simulated values were compared, with mean absolute error (MAE), root mean square error (RMSE), Nash–Sutcliffe modelling efficiency (NSE), and percent bias (PB) values of 2.2 cm, 3.4 cm, 0.79, and −7.1% and 5.2 cm, 7.0 cm, 0.50, and −14.1%, respectively. The empirical model proposed by Amin and Ekhmaj (2006) (AE) demonstrated the highest accuracy when the estimations of Z were compared with measured and simulated values, with MAE, RMSE, NSE and PB values of 1.7 cm, 2.0 cm, 0.95 and 4.15% and 4.4 cm, 5.9 cm, 0.82 and 4.7%, respectively. The comprehensive rankings of available models in the present study indicate that the FY model is the most universally applicable, followed by the Li et al. (2022) (LY) model, with comprehensive indices of 0.960 and 0.936, respectively. This research can aid in the selection of universally applicable, reliable and straightforward empirical models for estimating wetting patterns in drip irrigation systems. Une estimation précise du rayon de surface mouillée (R) et de la profondeur verticale mouillée (Z) des modèles de mouillage dans les systèmes d'irrigation goutte à goutte est cruciale pour garantir l'efficacité de la conception de ces systèmes. Cette étude a fait la comparaison de 14 modèles empiriques pour estimer les modèles de mouillage de l'irrigation goutte à goutte en évaluant leur précision à l'aide de données de mesure publiées et de simulations HYDRUS‐2D/3D. La technique pour l'ordre de préférence par similarité de solution idéale (TOPSIS) a été utilisée pour classer complètement les modèles. Les résultats indiquent que le modèle empirique proposé par Fan et al. (2023) (FY) présentait la plus grande précision lorsque les estimations de R et les valeurs mesurées et simulées ont été comparées, avec l'erreur absolue moyenne (MAE), l'erreur quadratique moyenne (RMSE), l'efficacité de modélisation de Nash‐Sutcliffe (NSE) et les valeurs de biais en pourcentage (PB) de 2,2 cm, 3,4 cm, 0,79 et − 7,1% et 5,2 cm, 7,0 cm, 0,50 et − 14,1%, respectivement. Le modèle empirique proposé par Amin and Ekhmaj (2006) (AE) a démontré la plus grande précision lorsque les estimations de Z ont été comparées aux valeurs mesurées et simulées, avec des valeurs MAE, RMSE, NSE et PB de 1,7 cm, 2,0 cm, 0,95, et 4,15% et 4,4 cm, 5,9 cm, 0,82 et 4,7%, respectivement. Le classement complet des modèles disponibles dans la présente étude indique que le modèle FY est le plus universellement applicable, suivi par le modèle Li et al. (2022) (LY), avec des indices complets de 0,960 et 0,936, respectivement. Cette recherche peut aider à retenir des modèles empiriques universellement applicables, fiables et simples pour estimer les modèles de mouillage dans les systèmes d'irrigation goutte à goutte.